2014
DOI: 10.12691/aees-2-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Economic Analysis of the Wind Turbine Plant’s Draft for the Aksaray City

Abstract: This study presents energy and economic analysis of the wind turbine plant's draft for the Aksaray city. Fossil fuels are used for energy production that is giving the environmental damage and increasing the global warming. The countries utilize a renewable energy for decreasing the global warming's impacts. The wind energy is the one of the important renewable energy. In this study, drafting 1 [MW] of the wind turbine plant was calculated energy and economic analysis for the Aksaray city. When 1 [MW] of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…Numerous studies are conducted on power systems from energy and economic point of view. Taner and Demirci [13] presented energy and economic analysis of the wind turbine plant's draft for the Aksaray city. A 1 MW of the wind turbine plant was calculated for energy and economic analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies are conducted on power systems from energy and economic point of view. Taner and Demirci [13] presented energy and economic analysis of the wind turbine plant's draft for the Aksaray city. A 1 MW of the wind turbine plant was calculated for energy and economic analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For economics, the biggest issue is related to the investment cost (I d ), simulations ran by [27] has shown that investment cost is guide by the following equation:…”
Section: Conflict Points: Economics and Land Usementioning
confidence: 99%
“…Moreover, there are Thermodynamic Laws in nuclear energy studies [2]. Energy and exergy analysis studies are also applied in wind energy [3]. Different topics and advantages such as solar energy and fuel cell energy and exergy analyses are emphasized from renewable energy sources [4][5][6].…”
Section: A Brief Of Power Plantsmentioning
confidence: 99%